Contrecoup injury in traumatic temporal bone fracture - Asha'ari, Zamzil Amin; Raja Lope Ahmad, Raja Ahmad Al'konee; Ab Rahman, Jamalludin; Kamarudin, Norie Azilah; Wan Leman, Wan Ishlah (2011)
Objective : to study the prevalence and patterns of contrecoup injury in traumatic temporal bone fracture